The effect of ownership structure on initial return and post-listing liquidity: evidence from Bursa Malaysia - Ramlee, Roslily; Ali, Ruhani (2014)

(untitled)
In IPO market, the theory of liquidity as proposed by Booth and Chua (1996) suggest that higher initial return drives the broadness of shareholder base and thus may enhance post-listing liquidity of an initial public offering (IPO) stocks. Based on that hypothesis, this paper examines the sample of 299 Bursa Malaysia IPOs for years 1998-2008 and finds that market adjusted initial return has significant positive predictive power on broadness of initial shareholder base. Market adjusted initial return is positively correlated with the breadth of shareholders and negatively correlated with the proportion of five largest and non-block institutional shareholders. IPO companies with sizeable number of shareholders tend to have higher post-listing liquidity whereas the proportion of block-holders and five largest shareholders adversely affect the secondary market liquidity. These results provide evidence to Booth and Chua’s hypothesis. Initial return also has a direct positive effect on post-listing liquidity. The positive relationship between initial return and post-listing liquidity is stronger for IPO stock with substantial ownership by government. Concentrated ownership structure in IPO with government ownership has negative effect on their trading turnover but greater liquidity is achieved through lower transaction cost.